PEMBERDAYAAN IBU-IBU PKK DALAM PENGOLAHAN SAMPAH UPAKARA YADNYA MENJADI PUPUK KOMPOS GUNA MENINGKATKAN PEREKONOMIAN MASYARAKAT DESA ADAT MENGWI BADUNG - Ni Made Sukrawati; Anak Agung Raka; Ni Wayan Lysnia Pranika Wulandari (UNHI Press, 2023)
The purpose of this paper is to find out the regulations related to ceremonial waste in Bali by understanding the form of government responsibility for the management of ceremonial waste to be able to protect the environment based on Tri Hita Karana carried out by the community, which is stated in